Impaired Lymphocytes Development and Xenotransplantation of Gastrointestinal Tumor Cells in Prkdc-Null SCID Zebrafish Model - In Hye Jung; Yong-Yoon Chung; Dawoon E. Jung; Young Jin Kim; Do Hee Kim; Kyung-Sik Kim; Seung Woo Park (Neoplasia: An International Journal for Oncology Research, 2016)
Severe combined immunodeficiency (SCID) mice have widely been used as hosts for human tumor cell xenograft study. This animal model, however, is labor intensive. As zebrafish is largely emerging as a promising model system for studying human diseases including cancer, developing efficient immunocompromised strains for tumor xenograft study are also demanded in zebrafish. Here, we have created the Prkdc-null SCID zebrafish model which provides the stable immune-deficient background required for xenotransplantation of tumor cell. In this study, the two transcription activator-like effector nucleases that specifically target the exon3 of the zebrafish Prkdc gene were used to induce a frame shift mutation, causing a complete knockout of the gene function. The SCID zebrafish showed susceptibility to spontaneous infection, a well-known phenotype found in the SCID mutation. Further characterization revealed that the SCID zebrafish contained no functional T and B lymphocytes which reflected the phenotypes identified in the mice SCID model. Intraperitoneal injection of human cancer cells into the adult SCID zebrafish clearly showed tumor cell growth forming into a solid mass. Our present data show the suitability of using the SCID zebrafish strain for xenotransplantation experiments, and in vivo monitoring of the tumor cell growth in the zebrafish demonstrates use of the animal model as a new platform of tumor xenograft study.